Assessing the width of Gaussian density of states in organic semiconductors - Maddalena, Francesco; de Falco, Carlo; Caironi, Mario; Natali, Dario (Organic electronics, 2015)
[Display omitted] •The DOS width is assessed using MIS capacitors as test beds.•The DOS width is assessed without involving carrier mobility.•The approach is based on numerical fitting of Capacitance–Voltage curves.•Two semiconducting polymers, one of n-type and one of p-type are analyzed.•Extracted DOS widths allow to predict static characteristics of Thin Film Transistors. The Density of States (DOS) is an ingredient of critical importance for the accurate physical understanding of the optoelectronic properties of organic semiconductors. The disordered nature of this class of materials, though, renders the task of determining the DOS far from trivial. Its extraction from experimental measurements is often performed by driving the semiconductor out of thermal equilibrium and therefore requires making assumptions on the charge transport properties of the material under examination. This entanglement of DOS and charge transport models is unfavorable since transport mechanisms in organic semiconductors are themselves still subject of debate. To avoid this, we propose an alternative approach which is based on populating and probing the DOS by means of capacitive coupling in Metal Insulator Semiconductors (MIS) structures while keeping the semiconductor in thermal equilibrium. Assuming a Gaussian shape, we extract the DOS width by numerical fitting of experimental Capacitance–Voltage curves, exploiting the fact that the DOS width affects the spatial distribution of accumulated charge carriers which in turn concurs to define the MIS capacitance. The proposed approach is successfully tested on two benchmark semiconducting polymers, one of n-type and one of p-type and it is validated by verifying the robustness of the extraction procedure with respect to varying the insulator electrical permittivity. Finally, as an example of the usefulness and effectiveness of our approach, we study the static characteristics of thin film transistors based on the aforementioned polymers in the framework of the Extended Gaussian Disorder transport model. Thanks to the extracted DOS widths, the functional dependence of current on the gate voltage is nicely predicted and physical insight on transistor operation is achieved.